The liar's ball : the extraordinary saga of how one building broke the world's toughest tycoons - Ward, Vicky (John Wiley & Sons, 2014)
The Lỉa's ball is about the desperate scamble that ensued when the wold's most expensive building went on the auction block. The iconic GM building brought out the best and worst in New York's real estate royalty, and led a few of them to ruin. But as author and former vanity fair contrubuting editor vicky ward discoverd, the story of the GM building is about much more than real estate.